Primary cardiac angiosarcoma: a case report - Yuan, Yin; Yu, Zhao; Diao, Wenjie; He, Zelai; Ding, Jianming; Wang, Gengming (Frontiers in Oncology, 2025)
Primary cardiac tumors are extremely rare, with an incidence rate ranging from only 0.17% to 0.33%. Clinically, their diagnosis is often delayed due to nonspecific clinical symptoms. This paper reports a case of primary cardiac angiosarcoma (PCAS) pathologically confirmed via surgery, presenting with recurrent palpitations during exertion as the initial symptom. The patient subsequently developed bilateral lung and liver metastases and received chemotherapy. Through a comprehensive review of the literature, this report explores the diagnostic and therapeutic strategies for PCAS, with a focus on analyzing the mechanisms underlying the atypical disease course, the rationale for treatment decisions, and the key clinical insights.